Qing-Kai-Ling Injection Induces Immediate Hypersensitivity Reaction via the Activation of Anaphylatoxin C3 - Gao, Yuan; Qi, Ruijuan; Zhang, Xiaoyu; Xu, Xudong; Han, Yixin; Fei, Qiaoling; Wang, Xiaojing; Cai, Runlan; Sun, Guibo; Qi, Yun (Frontiers in Pharmacology, 2020)
Background and Objective: Qing-Kai-Ling (QKL) is derived from a famous ancient Chinese patent medicine Angong Niuhuang pills (ANP) which has been used across Asia, especially in China, for the treatment of “febrile disease,” such as stroke, encephalitis and meningitis for hundreds of years. As an extract of ANP without heavy metal, the clinical applicability of QKL is more intensive, of which its injection is commonly used in acute and serious diseases. This study aims to clarify the potential mechanisms of immediate hypersensitivity reaction (IHR) induced by QKL injection (QKLI). Methods: β-hexosaminidase release assay was performed on the human mast cell line LAD2 and mouse peritoneal mast cells. T helper 2 (Th2) immunity-amplified mice were prepared by aluminum adjuvant. Anaphylactic shock was detected by measuring rectal thermometry in propranolol-pretreated mice. For evaluating microvascular permeability, Evans Blue extravasation assay was used. Serum total IgE (tIgE) and the activated complement-derived anaphylatoxin C3 (C3a) levels were measured by ELISA. Results: QKLI was unable to elevate serum tIgE level in the Th2 immunity-amplified mice, but can increase vasopermeability and trigger anaphylaxis after the first injection. By screening seven fractions of QKLI, only the extract of Isatidis Radix (Isatis tinctoria L.) induced hindpaw Evans Blue extravasation, which was disappeared in Isatidis Radix-free QKLI. Mechanism study indicated that QKLI or Isatidis Radix-caused IHR could be blocked by the antagonists for histamine or C3a, rather than PAF or C5a. Consistently, QKLI and Isatidis Radix could also directly activate human serum complement-derived anaphylatoxin 3 (C3) in vitro with the half effective concentration values of 0.69% and 218.6 μg/ml, respectively. Conclusion: QKLI-IHR is complement activation-related pseudoallergy, rather than an IgE-mediated allergy. QKLI activates C3 and might consequently provoke mast cells to release histamine, which is a principal effector of its IHR. The pseudoallergic reaction induced by QKLI was attributed to the extract of Isatidis Radix. This study suggests a potential therapeutic strategy for the prophylaxis and treatment of QKLI-IHR.